A systematic review of the health-financing mechanisms in the Association of Southeast Asian Nations countries and the People’s Republic of China: Lessons for the move towards universal health coverage - Myint, Chaw-Yin (PLoS One, 2019)
We systematically review the health-financing mechanisms, revenue rising, pooling, purchasing, and benefits, in the Association of Southeast Asian Nations (ASEAN) and the People’s Republic of China, and their impact on universal health coverage (UHC) goals in terms of universal financial protection, utilization/equity and quality. Two kinds of sources are reviewed: 1) academic articles, and 2) countries’ health system reports. We synthesize the findings from ASEAN countries and China reporting on studies that are in the scope of our objective, and studies that focus on the system (macro level) rather than treatment/technology specific studies (micro level).The results of our review suggest that the main sources of revenues are direct/indirect taxes and out of pocket payments in all ASEAN countries and China except for Brunei where natural resource revenues are the main source of revenue collection. Brunei, Indonesia, Philippines, Malaysia, and Viet Nam have a single pool for revenue collection constituting a national health insurance. Cambodia, China, Lao, Singapore, and Thailand have implemented multiple pooling systems while Myanmar has no formal arrangement. Capitation, Fee-for-Service, DRGs, Fee schedules, Salary, and Global budget are the methods of purchasing in the studied countries. Each country has its own definition of the basic benefit package which includes the services that are perceived as essential for the population health. Although many studies provide evidence of an increase in financial protection after reforming the health-financing mechanisms in the studied countries, inequity in financial protection continue to exist. Overall, the utilization of health care among the poor has increased as a consequence of the implementation of government subsidized health insurance schemes which target the poor in most of the studied countries. Inappropriate policies and provider payment mechanisms impact on the quality of health care provision. We conclude that the most important factors to attain UHC are to prioritize and include vulnerable groups into the health insurance scheme. Government subsidization for this kind of groups is found to be an effective method to achieve this goal. The higher the percentage of government expenditure on health, the greater the financial protection is. At the same time, there is a need to weigh the financial stability of the health-financing system. A unified health insurance system providing the same benefit package for all, is the most efficient way to attain equitable access to health care. Capacity building for both administrative and health service providers is crucial for sustainable and good quality health care.